A goal-oriented anisotropic hp-mesh adaptation method for linear convection–diffusion–reaction problems. (1st November 2019) - Bartoš, Ondřej; Dolejší, Vít; May, Georg; Rangarajan, Ajay; Roskovec, Filip
Abstract: We deal with the numerical solution of linear convection–diffusion–reaction equations using the h p -variant of the discontinuous Galerkin method on triangular grids. We develop a mesh adaptive algorithm which modifies the size and shape of mesh elements and the corresponding polynomial approximation degrees in order to decrease the error in a target functional under the given tolerance. We recall some theoretical results and describe in detail several technical aspects of this approach. Numerical experiments demonstrating the accuracy, efficiency and robustness of the algorithm are presented.